Functional Characterization of a Novel Oligoalginate Lyase of Stenotrophomonas maltophilia KJ-2 Using Site-Specific Mutation Reveals Bifunctional Mode of Action, Possessing Both Endolytic and Exolytic Degradation Activity Toward Alginate in Seaweed Biomass - Chu, Yoo Jung; Kim, Hae Sol; Kim, Myung Sun; Lee, Eun Yeol; Kim, Hee Sook (Frontiers in Marine Science, 2020)
A novel oligoalginate lyase from the marine bacterium, Stenotrophomonas maltophilia KJ-2, completely depolymerizes alginate to monomers with generation of oligomer intermediates. In order to analyze whether KJ-2 oligoalginate lyase has endolytic and exolytic alginate lyase activities, five mutants were developed and characterized using homology modeling based on the crystal structure of Alg17c, an exolytic oligoalginate lyase from Saccharophagus degradans 2-40. The important residues of Tyr238, Arg241, Arg418 and Glu644, which were predicted to be located within hydrogen bonding distance of the non-reducing end of alginate during exolytic catalysis, were mutated to Phe, Ala, Ala and Ala, respectively. Exolytic activities of Arg241Ala, Glu644Ala and Arg241Ala_Glu644Ala mutants decreased compared to the wild type, indicating that Arg241 and Glu644 are key residues for exolytic catalysis. Interestingly, these mutants produced oligomers as the main product due to inherent endolytic degradation activity. These mutational characterization results showed that KJ-2 oligoalginate lyase possesses catalytic domains for both inherent endolytic and exolytic activities.